Maternal oral supplementation with Saccharomyces boulardii I-1079 during gestation and early lactation impacts the early growth rate and metabolic profile of newborn puppies - Bendahmane, Ilyas; Garrigues, Quentin; Apper, Emmanuelle; Mugnier, Amélie; Svilar, Ljubica; Martin, Jean-charles; Chastant, Sylvie; Meynadier, Annabelle; Mila, Hanna (Frontiers in Nutrition, 2025)
Nutritional programming is a manipulation of fetal and neonatal development through maternal feeding. In humans and pigs, maternal yeast supplementation was demonstrated as a promising approach to positively to modulate newborns' health. This study aimed to investigate the effects of Saccharomyces cerevisiae var. boulardii CNCM I-1079 (SB) supplementation in pregnant and lactating bitches on the newborns' early growth rate (EGR, between birth and 2 days of life), metabolic profiles, and the association between both of them. A total of 17 female dogs and their 81 puppies were included. From day 28 of gestation until the end of the study, bitches were divided into two groups, one of which received orally 1.3 × 109 colony forming units of live yeast per day. Puppies from mothers receiving the live yeast were defined as the SB group (n = 40) and the others were defined as the placebo group (n = 4 1). For each puppy, EGR was calculated, and blood and urine samples were collected at D2 for metabolome analysis using liquid chromatography-mass spectrometry (LCMS). Puppies from the SB group presented higher EGR compared with the placebo group (12% vs. 7%; p = 0.049). According to the Sparse Partial Least Squares Discriminant Analysis (sPLS-DA), both urine and serum metabolome profiles were significantly different between the two groups with a total of 29 discriminating metabolites in urine and serum. Fourteen of them were implicated in the nitrogen metabolism pathway including, gamma-aminobutyrate, 3-methyl-l-histidine and xanthosine (less abundant in SB compared with placebo group, all p < 0.05), adenine, aspartate and proline (more abundant in SB compared with placebo group, all p < 0.05). Metabolic pathways pointed to proline synthesis, a crucial component in collagen synthesis and osteoarticular system development. Urinary proline abundance was positively correlated with EGR (r = 0.45; p < 0.001). These findings highlight the potential benefits of maternal supplementation with SB promoting early neonatal growth, essential for the neonatal survival, through nitrogen metabolism orientation.